Understanding deinstitutionalization policies for older adults through sarcopenia and the place of aging in Spain - María Ángeles Tortosa-Chuliá; Natalia Cezón-Serrano; Anna Arnal-Gómez; Mercè Balasch-Bernat; Trinidad Sentandreu-Mañó; Maria Àngels Cebrià i Iranzo (Scientific Reports)
Abstract To support deinstitutionalization policies in Spain, it’s useful to understand sarcopenia determinants. This study analyzed 267 community-dwelling and institutionalized older adults, measured sarcopenia using the European Working Group of Sarcopenia in Older People 2 (EWGSOP2) algorithm and looked for the role of place of aging among a set of social, economic, psychological and environmental variables. Findings reveal that the place of aging might have a significant relationship with sarcopenia in Spanish older adults and that a large proportion of older adults with sarcopenia could end up living in institutions. These results are in accordance with some actions lines of the deinstitutionalization Spanish strategy and point out that it would be necessary to prevent sarcopenia, mainly in the oldest, in those with low cognitive status and quality of life in order to promote deinstitutionalization and retain older adults in their community as much as possible.